A key-predistribution-based weakly connected dominating set for secure clustering in DSN - Pathan, Al-Sakib Khan; Hong, Choong Seon (Springer-Verlag, Berlin, Germany, 2006)
The intent of this paper is to propose an efficient approach of secure clustering in distributed sensor networks. The clusters or groups in the network are formed based on offline rank assignment and key-predistribution. Our approach uses the concept of weakly connected dominating set to reduce the number of cluster heads in the network. The formation of clusters in the network is secured as the secret keys are distributed and used in an efficient way to resist the inclusion of any hostile entity in the clusters. Along with the description of our mechanism, we present an analysis and comparison to justify the efficiency of our approach.